Nigeria - A Fiscal Agenda for Change : Public Expenditure Management and Financial Accountability Review, Volume 2. Executive Summary - World Bank (Washington, DC, 2012)
This report reviews the trends in expenditure patterns in public financial management (PFM) in Nigeria since 2001, and assesses the impact thus far of the ongoing government reform efforts. The public expenditure management and financial accountability review (PEMFAR) covers areas that have been traditionally undertaken by separate Bank reports such as the public expenditure reviews (PER), the country financial accountability assessment (CFAA), and the country procurement assessment review (CPAR). This analysis covers fiscal policies and performance at both federal and state government levels. The PEMFAR is a consolidated diagnostic tool designed to enhance Bank, development partners' and member countries' knowledge of PFM arrangements and reform challenges. The core objective of the Nigeria PEMFAR is to advise the Government (federal and participating states) on how (i) to better focus and sequence its PFM, including the procurement reform agenda within a broader economic reform framework, and (ii) identify directions and instruments of restructuring its expenditure patterns on both macro and sectoral levels. The PEMFAR also aims to inform international development partners on how they could provide more efficient support for the PFM reforms in Nigeria by identifying the main bottlenecks within the existing reform process.